Effective robotics programming with ROS : find out everything you need to know to build powerful robots with the most up-to-date ROS /: find out everything you need to know to build powerful robots with the most up-to-date ROS. (2016) - Mahtani, Anil; Sánchez, Luis; Fernández, Enrique (Fernández Perdomo); Martinez, Aaron
No abstract available